Prospective clinical study using radiostereometric analysis (RSA) to evaluate fixation of a modular cemented polished femoral stem. Issue 2 (March 2021) - Richardson, C Glen; Laende, Elise K; Gross, Michael; Dunbar, Michael J
Background: The long-term clinical success of cemented polished tapered femoral components has been demonstrated in prospective as well as registry studies. This stem design type has also been well studied with radiostereometric analysis (RSA) and provides a standard to evaluate alternative designs of polished tapered cemented femoral components. This prospective study evaluates the subsidence of a polished cemented stem with a modular neck design utilising RSA. Methods: 26 patients were prospectively enrolled in the study and 23 were available for RSA analysis at 2 years. Results: The average subsidence of the femoral implant was 1.1 mm (SD 0.4 mm) at 2 years post operation. There were no revisions in this group, specifically no failures of the modular stem-neck design as has been seen with other implants. Conclusions: The RSA subsidence pattern at 2 years of this cemented femoral stem is similar to other successful designs with long-term follow-up. The implications over time of stem neck modularity for cemented polished tapered femoral components requires further evaluation.